Mechanical Properties for Elephant Dung and its Utilization as a Raw Material Composites Sheet: A Study - Kumar, Rohit; Ramratan; Kumar, Anupam; Smagh, Rajinder Singh (Asian Journal of Engineering and Applied Technology, 2021)
Elephant dung is an excellent source of cellulosic fiber that is a basic requirement for paper making. But they contributed to very small percentage production of elephant dung. So, researchers are trying to find a new area of utilization of elephant dung fiber pulp as in reinforcement’s polymer composite. In this experiment element dung fiber pulp in the natural fiber component chemically treated with alkaline and soda AQ solution in this study, it has been aimed to use elephant dung fiber pulp in composite material and to study mechanical properties of the produced material. The produced composite samples were then characterized using tensile test, Izod impact test, thickness test. The fracture surface of the polymer composite sample was also inspected with the help of SEM. The content of elephant dung fiber pulp is varied (35%, 45%, 55%) weight percentage whereas the epoxy resin is varied (50%, 40%, 30%) percentage is kept constant 15% in hardener. The entire sample has been tested in a universal testing machine as per ASTM standard for tensile strength and impact strength. It is observed that composite with 35% fiber pulp is having the highest tensile strength of 4mm 6.445 Mpa and 8mm 11.80 Mpa. The impact strength of composite with 35% fiber pulp washes highest than 45% to 55% dung fiber pulp. This produces composite sheet will be used for the surfboards, sporting goods, building panel this not only reduces the cost but also save from environmental pollution.